The Effect of Online Customer Reviews, Online Customer Ratings, and Product Diversity on Purchase Decisions of Generation Z - Shofi Rahmadannia Putri; Siti Hanila; Muhammad Rahman Febliansa (Utami Publisher, 2026)
Changes in consumption behavior due to the development of digital This study aims to analyze the influence of online customer reviews, online customer ratings, and product diversity Purchase Decisions of Generation Z, Bengkulu City. The results show that the multiple linear regression equation obtained is Y = 15.186 + 0.265X₁ + 0.285X₂ + 0.295X₃ + e. The coefficients are positive, meaning that there is a positive or unidirectional relationship between the variables of online customer reviews (X₁), online customer ratings (X₂), and product diversity (X₃), with a value of 0 (zero) on the purchase decisions (Y) of Generation Z, Bengkulu City. The results show that the online customer review (X₁) test indicates a t-count of 2.706 > t-table 1.654 and a significance of 0.008 < 0.05, so Ha hypothesis is accepted and Ho is rejected, meaning that online customer reviews have a positive and significant effect on Generation Z's purchase decisions, Bengkulu City. The results of the online customer rating test (X₂) show t-count of 1.896 > t-table 1.654 and a significance of 0.006 < 0.05, so the results of Ha hypothesis are accepted and Ho hypothesis is rejected, meaning that online customer ratings have a positive and significant effect on Generation Z's purchase decisions in Bengkulu City. The results of the product diversity test (X₃) show that t-count is 2.926 > t-table 1.654 and the significance is 0.004 < 0.05, so the Ha hypothesis is accepted and the Ho hypothesis is rejected, meaning that product diversity has a positive and significant effect on Generation Z's purchase decisions in Bengkulu City. Based on a comparison of the calculated f count with the table f value, the calculated f value is greater than the table f value, namely 25.322 > 2.66, and R² has a value of 0.614, which means that 61.4% of the variation in purchase decisions can be explained by the variables of online customer reviews, online customer ratings, and product diversity, while the rest is influenced by other factors outside this study.